Using Optimal Test Assembly Methods for Shortening Patient‐Reported Outcome Measures: Development and Validation of the Cochin Hand Function Scale‐6: A Scleroderma Patient‐Centered Intervention Network Cohort Study. Issue 11 (9th October 2016) - Levis, Alexander W.; Harel, Daphna; Kwakkenbos, Linda; Carrier, Marie‐Eve; Mouthon, Luc; Poiraudeau, Serge; Bartlett, Susan J.; Khanna, Dinesh; Malcarne, Vanessa L.; Sauve, Maureen; van den Ende, Cornelia H. M.; Poole, Janet L.; et al.
Abstract : Objective: To develop and validate a short form of the Cochin Hand Function Scale (CHFS), which measures hand disability, for use in systemic sclerosis, using objective criteria and reproducible techniques. Methods: Responses on the 18‐item CHFS were obtained from English‐speaking patients enrolled in the Scleroderma Patient‐Centered Intervention Network Cohort. CHFS unidimensionality was verified using confirmatory factor analysis, and an item response theory model was fit to CHFS items. Optimal test assembly (OTA) methods identified a maximally precise short form for each possible form length between 1 and 17 items. The final short form selected was the form with the least number of items that maintained statistically equivalent convergent validity, compared to the full‐length CHFS, with the Health Assessment Questionnaire (HAQ) disability index (DI) and the physical function domain of the 29‐item Patient‐Reported Outcomes Measurement Information System (PROMIS‐29). Results: There were 601 patients included. A 6‐item short form of the CHFS (CHFS‐6) was selected. The CHFS‐6 had a Cronbach's alpha of 0.93. Correlations of the CHFS‐6 summed score with HAQ DI (r = 0.79) and PROMIS‐29 physical function (r = −0.54) were statistically equivalent to the CHFS (r = 0.81 and r = −0.56). The correlation with the full CHFS was high (r = 0.98). Conclusion: The OTA procedure generated a valid short form of the CHFS with minimal loss of information compared to the full‐length form. The OTA method used was based on objective, prespecified criteria, but should be further studied for viability as a general procedure for shortening patient‐reported outcome measures in health research.